2022
DOI: 10.7150/ijms.72334
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Atrial Fibrillation Increases with Earlier Onset of Obesity: A Mendelian Randomization Study

Abstract: Background: Obesity is a well-established risk factor for atrial fibrillation (AF). Previous epidemiological research on obesity and AF often focused on adult populations and now broadened to earlier in life. Therefore, this study aimed to determine the relationships between obesity at different periods of life and the risk of AF. Methods: A two-sample Mendelian randomization (MR) study design using summarised data from 6 genome-wide association studies (GWASs) was employed in this study. Single nucleotide pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…BMI has long been a well-recognized metric for nutritional assessment because of its simplicity and established relationships with associated comorbidities. Previous studies have shown that a high BMI is a risk factor for the development of HF and atrial fibrillation, a finding that is consistent with the results of our MR analysis [ [23] , [24] , [25] , [26] , [27] ]. However, there is still the so-called "obesity-survival paradox [ [28] , [29] , [30] , [31] ]."…”
Section: Discussionsupporting
confidence: 93%
“…BMI has long been a well-recognized metric for nutritional assessment because of its simplicity and established relationships with associated comorbidities. Previous studies have shown that a high BMI is a risk factor for the development of HF and atrial fibrillation, a finding that is consistent with the results of our MR analysis [ [23] , [24] , [25] , [26] , [27] ]. However, there is still the so-called "obesity-survival paradox [ [28] , [29] , [30] , [31] ]."…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies leveraging MR showcase its statistical power in revealing certain underlying factors that increase disease risks. Within the context of AF, MR surveys have accentuated the spectrum of risk factors, ranging from obesity 68 and obstructive sleep apnoea (OSA) 69 to even a 1‐unit standard deviation increase in childhood body mass index, 68 birth weight 68 and height 70 all of which indicate an elevated risk of AF 71 . Similarly, when leveraged to understand the aetiology of HF, it reveals a spectrum of risk factors, including higher diastolic and systolic blood pressures, elevated triglyceride levels, genetic predisposition to AF and coronary artery disease as significant contributors to heightened HF risk.…”
Section: Gwas and Mendelian Randomisationmentioning
confidence: 99%
“…Interestingly, an analysis by Zhou et al, which pooled data from 6 genome-wide association studies, demonstrated that the risk of AF in adulthood increases with earlier onset of obesity. They found that a 1 standard deviation increase in adult obesity, childhood BMI, and birth weight was associated with a 13%, 18%, and 26% increased risk of AF in adulthood, respectively [ 35 ]. These interesting findings may thus point to a causal relationship between obesity and AF.…”
Section: Epidemiology Of Obesity and Afmentioning
confidence: 99%